2018
DOI: 10.1259/bjr.20180137
|View full text |Cite
|
Sign up to set email alerts
|

Improving image quality with model-based iterative reconstruction at quarter of nominal dose in upper abdominal CT

Abstract: The public has been increasingly concerned about radiation exposure. Medical radiation exposure is no exception 1 . CT has become more prevalent. Meanwhile, the dose received by the patient has increased. A survey shows that medical exposure constituted nearly half of the total radiation exposure of the US population from all sources in 2006, and CT was a major contributor. 2 As a non-invasive means of inspection, CT and MRI are the two major imaging modalities and have almost replaced exploratory laparotomy f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…In the past, multiple approaches for dose reduction in MDCT-based body composition imaging were performed. Amongst others, Chang et al showed the possibility of tube current reduction up to 50% of original doses in liver imaging with a preservation of image quality and contrast-to-noise ratio and stable quantitative measures (35,36). Furthermore, Yamada et al proved the feasibility of lowering radiation doses to 30% of the original dose in imaging visceral and subcutaneous adipose tissue, which constitute the largest share of human fat deposition localizations (37).…”
Section: B Amentioning
confidence: 99%
“…In the past, multiple approaches for dose reduction in MDCT-based body composition imaging were performed. Amongst others, Chang et al showed the possibility of tube current reduction up to 50% of original doses in liver imaging with a preservation of image quality and contrast-to-noise ratio and stable quantitative measures (35,36). Furthermore, Yamada et al proved the feasibility of lowering radiation doses to 30% of the original dose in imaging visceral and subcutaneous adipose tissue, which constitute the largest share of human fat deposition localizations (37).…”
Section: B Amentioning
confidence: 99%
“…IR reduces image noise for the same radiation dose, or alternatively allows for radiation dose reduction for the same image quality [56]. This has been demonstrated in phantom and clinical settings for pancreatic evaluation (36-60% radiation dose saving), even on wide-16cm-detector systems [57][58][59][60][61]. A specific type of IR known as model-based IR can further reduce radiation dose by up to 75% [60].…”
Section: Multi-detector Computerized Tomographymentioning
confidence: 99%
“…This has been demonstrated in phantom and clinical settings for pancreatic evaluation (36-60% radiation dose saving), even on wide-16cm-detector systems [57][58][59][60][61]. A specific type of IR known as model-based IR can further reduce radiation dose by up to 75% [60]. Lin et al evaluated 1.25 thin axial pancreatic phase CT images and found that IRreconstructed images, especially model-based IR, better depicted the pancreatic duct [62].…”
Section: Multi-detector Computerized Tomographymentioning
confidence: 99%